Analisis Kadar Timbal (Pb) Dan Serum Glutamic Pyruvic Transaminase (SGPT) Pada Pengemudi Ojek Online Di Kota Denpasar, Bali - rahayu artini yuan; I Wayan Tanjung Aryasa; Putu Lakustini Cahyaningrum (Universitas Muhammadiyah Surabaya, 2021)
motorcycle taxi is a transportation service with communication technology in the world. The average mobility of online motorcycle taxi drivers is between 8-12 hours per day, this will certainly affect the physical condition and function of the drivers' organs, especially motorbike drivers. The purpose of this study was to determine the health status of online motorcycle taxi drivers, which was reviewed from liver function tests, namely serum glutamic pyruvic transaminase (SGPT) and exposure to heavy metal lead (Pb). This study used an experimental experimental research design pretest-posttest control group design. In this study, there was an increase in the levels of SPGPT and lead (Pb) for online motorcycle taxi drivers in Denpasar City with the SGPT level for male drivers being 14.14% and for women 19.62% and lead (Pb) levels for male drivers. -Male is 2.61% and female 5.14%.